TINJAUAN YURIDIS TERHADAP PENIPUAN HAK MILIK ATAS TANAH YANG DILAKUKAN OLEH MAFIA TANAH BERDASARKAN PASAL 378 KITAB UNDANG-UNDANG HUKUM PIDANA - Sang Ayu Made Ary Kusumawardhani, S.H., M.H. (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
The term criminal act comes from a term known in criminal law, namely strafbaarfeit. Even though this term is found in the Dutch WvS, there is no official explanation regarding the translation of the term